The Position of the Murabahah Contract in BSI Griya Hasanah Financing at BSI KC Palangkaraya Diponegoro - Syawaliah, Syawaliah; Muzalifah, Muzalifah; Adlina, Fadiah (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This study aims to determine the position of the murabahah contract in BSI Griya Hasanah Financing at Bank Syariah Indonesia Palangkaraya Diponegoro Branch Office. In addition, to find out how the implementation of BSI Griya Hasanah financing products with murabahah contracts. The method used is qualitative with a descriptive analytical method. Data collection techniques through interviews with Bank Syariah Indonesia KC Palangkaraya Diponegoro, as well as a documentation approach and also literature studies related to this study. The results of the study found that the BSI Griya Hasanah financing product is appropriate if paired with a murabahah contract because in principle the transaction, the Islamic bank will purchase the house or apartment desired by the customer (the bank acts as the homeowner) and then sell the house or apartment to the customer in installments. This murabahah contract also has a strong foundation from the three basic laws of Islam, the Qur'an, Hadith and Ijma. Based on Q.S Al-Baqarah:275, hadith from Suhaib Ar-Rumi r.a and Fatwa of the National Sharia Council No. 04/DSN-MUI/2000 concerning murabahah financing and multi-service financing No. 44/DSN-MUI/VIII/2004.